Outsiders Within: College Sport as an Avenue to Integrate International Students - Xiaochen Zhou; Anthony Pizzo; Daniel C. Funk (Journal of Intercollegiate Sport, 2021)
The increasingly volatile social, cultural, and political environment in the United States has made it difficult for U.S. institutions of higher learning to retain and integrate international students, especially those from East Asian countries. Drawing upon social identity theory and the acculturation process, this study explored how college sport contributes to international students’ university identification using narrative interviews with East Asian international students who attended college football events at a U.S. university. Findings revealed that international students identified with their co-national peers for socialization purposes at football events and identified with the football spectator subgroup through the influence of domestic students, which contributed to university identity. Theoretically, our research highlighted the dynamics between sport identification, university identity, and acculturation by showing how college sport spectatorship can foster university identification but also create cultural distance within the university community. Findings also offer practical guidelines on how universities can use college sport to initiate organic social interactions between students from different cultures and empower international students to identify as essential members of universities.